Caridina biyiga sp. nov., a new freshwater shrimp (Crustacea: Decapoda: Atyidae) from Leichhardt Springs, Kakadu National Park, Australia, based on morphological and molecular data, with a preliminary illustrated key to Northern Territory Caridina - Short, John W.; Page, Timothy J.; Humphrey, Christopher L. (Zootaxa, 2019)
Caridina biyiga sp. nov. is described from Leichhardt Springs, Kakadu National Park, Northern Territory, Australia, based on morphological and molecular data. The new species is highly distinctive among its congeners in having the dactylus of pereiopod 5 similar to the dactyli of pereiopods 3–4 and lacking the comb-like row of spiniform setae typical of the genus. The branchial formula is also distinctive for the genus in lacking an arthrobranch at the base of pereiopod 1 and in having a vestigial epipod on maxilliped 1. Despite the distinctive morphology of the new species, the molecular data did not provide strong support for the recognition of a new genus. Phylogenetic analyses of Australian Caridina using the mitochondrial 16S rDNA gene fragment placed the new species in a well-supported clade containing at least one typical species of Caridina. Within this clade, referred to as the ‘thermophila’ group, Kimura 2-parameter (K2P) genetic distances of 16S rDNA between the new species and sister taxa ranged from 5.1–6.0%. Analyses using the mitochondrial 3’ COI gene fragment from species of the ‘thermophila’ group yielded K2P genetic distances between the new species and its sister taxa ranging from 10.4–15.1%. A preliminary illustrated key to Northern Territory Caridina is provided. The conservation significance of Leichhardt Springs and its aquatic fauna are also briefly discussed.